Comparison of Supracostal and Infracostal Access For Percutaneous Nephrolithotomy: A Systematic Review and Meta-Analysis - He, zhaohui; Tang, Fucai; Lu, Zechao; He, Ye; Wei, Genggeng; Zhong, Fangling; Zeng, Guohua; Wu, Weizhou; Yan, Lemin; Li, Zhibiao (Urology Journal, 2019)
Purpose: In this meta-analysis, we aimed to compared efficacy and safety of supracostal and infracostal access for percutaneous nephrolithotomy (PCNL). Materials and Methods: We included eligible studies from PubMed, EMBASE, Cochrane Library, Web of Science and China National Knowledge Infrastructure. Literature searching, quality assessment and data extraction were performed by two independent reviewers. Data were analyzed by RevMan software. Binary and continuous variables were calculated as odds ratios (OR) and mean difference (MD). Results: Two prospective comparative studies and seven retrospective observational studies were included in the meta-analysis, which contained 1,024 cases of supracostal access and 1,249 cases of infracostal access for PCNL. The supracostal access resulted in a significant reduced mean hemoglobin (95% CI: 0.26-3.46, MD = 1.86 g/L, P = .02) and a higher incidence of hydrothorax (95% CI: 4.77-22.95: OR = 10.47, P < .00001) compared to infracostal access. However, there no difference between supracostal and infracostal access regarding additional procedures (95% CI: 0.70-1.69, OR = 1.09, P = .71), stone-free rate (95% CI: 0.80-1.72, OR = 1.18, P = .41), length of hospital stay (95% CI: -0.03-0.37, MD = 0.17 day, P = .10), and occurrence of fever (95% CI: 0.95-2.03, OR = 1.39, P = .09) and blood transfusion (95% CI: 0.45-1.70, OR = 0.88, P = .70). No publication bias was identified in the study. Conclusion: Supracostal access was effective, but not as safe as infracostal access PCNL due to a higher risk of reduced hemoglobin and hydrothorax. Therefore, infracostal access should be the preferred safe and effective approach recommended for PCNL. When a supracostal puncture is performed, essential precautions to avoid hemoglobin loss and hydrothorax should be used.